ANALISIS PERUBAHAN TEMPERATUR INDUKSI MOTOR 3 PHASE BERBASIS FUZZY INFERENCE SYSTEM (FIS) - Fajar Pujiyanto; Eka Darmana (JURNAL SAINS DAN TEKNOLOGI MARITIM, 2022)
The three-phase induction motor is an alternative to changing the diesel engine as the main driver in the industrial world. This transition is aimed at energy efficiency and reducing air pollution from diesel engine exhaust gases. It was chosen because it is easy to operate, quiet and low operating costs. Induction motors are used for driving water pumps to as the main propulsion on board vessels. Constraints and failures of induction motor components when operating, cause a decrease in performance and risk of damage. This is due to winding disturbances, increasing motor temperature, unbalanced stator and rotor, broken rotor shafts, air gap eccentricity, motor load, mechanical and environmental effects. The cause of motor damaged is increased temperatures on the motor side. It occurs due to unbalanced phase voltage (UPV), unbalanced magnet pull (UMP) and motor load (ML). This journal discusses three factors and their effect on motor temperature based on Fuzzy Inference System (FIS). FIS analysis is used to simulate changes in motor temperature which are influenced by the variable values of these three factors. This paper uses a qualitative descriptive method with literature reviews and data analysis using FIS in a Matlab application. The analysis of the change in temperature of an induction motor with the three parameters based on FIS has been successfully carried out. The result of study concludes that UPV and UMP are the dominant factors as a cause of temperature changes in the induction motor compared to ML).Ådnanes, A. K. (2003). Maritime electrical installations and diesel electric propulsion. ABB AS Marine. http://citeseerx.ist.psu.edu/viewdoc/download?doi=10.1.1.115.966&rep=rep1&type=pdfAdvernesia. (2017). What is MATLAB and its Uses. Article/Id_ID.Ardana, I. W. R., & Sutawinaya, I. P. (2017). Pemodelan Sistem Kontroler Logika Fuzzy Pada Pengaturan Kecepatan Motor Induksi Menggunakan Perangkat Lunak Matlab / Simulink. Matrix : Jurnal Manajemen Teknologi Dan Informatika, 7(1), 1. https://doi.org/10.31940/matrix.v7i1.504Bergmeijer, P. (1992). The International Convention for the Prevention of Pollution from Ships. Ports As Nodal Points in a Global Transport System, 111(50), 259–270. https://doi.org/10.1016/b978-0-08-040994-8.50026-7Bonnett, A. H., & Soukup, G. C. (1986). in Squirrel Cage Induction Motors. I(6), 1165–1173.Bonnett, A. H., & Soukup, G. C. (1992). Cause and Analysis of Stator and Rotor Induction Motors. IEEE Transactions on Industry Applications, 28(4), 921–937.Hall, D. T. (1999). KNOWLEDGE MARINE Second Edition.International, C., Commission, E., Deshpande, V., Power, C., & No, O. (2004). Internationale International Standard. Order A Journal On The Theory Of Ordered Sets And Its Applications, 1997, 1–25.Kliman, G. B., Premerlani, W. J., Koegl, R. A., & Hoeweler, D. (1996). New approach to on-line turn fault detection in AC motors. Conference Record - IAS Annual Meeting (IEEE Industry Applications Society), 1, 687–693. https://doi.org/10.1109/ias.1996.557113Kusumadewi, S. (2003). Artificial Intelligence (Techniques and Applications). Graha Ilmu.McCoy, Gilbert A.; Douglass, J. G. (2014). Premium efficiency motor selection and application guide - A handbook for industry. 136. https://www.energy.gov/sites/prod/files/2014/04/f15/amo_motors_handbook_web.pdfMelka, B., Smolka, J., Hetmanczyk, J., & Lasek, P. (2019). Numerical and experimental analysis of heat dissipation intensification from electric motor. Energy, 182, 269–279. https://doi.org/10.1016/j.energy.2019.06.023Motors and Generator Section. (2009). NEMA Standards Publication MG 1-2009. 552, 775. https://law.resource.org/pub/us/cfr/ibr/005/nema.mg-1.2009.pdfMustafa, Demetgul, Muhammet, U. (Ed.). (1993). Parameter Estimation, Condition Monitoring and Diagnosis of Electrical Machines. 1993 (1st ed.). Janeza trdine 9. 51000 Rijeka, Croatia. https://doi.org/http://dx.d0i.org/10.5772/63169Nandi, S., Toliyat, H. A., & Li, X. (2005). Condition monitoring and fault diagnosis of electrical motors - A review. IEEE Transactions on Energy Conversion, 20(4), 719–729. https://doi.org/10.1109/TEC.2005.847955On, L. N. (n.d.). Lecture Notes on Machine-Ii.PP. (1999). Pp Ri No 41 Tahun 1999 Tentang Pengendalian Pencemaran Udara. Peraturan Pemerintah No. 41 Tentang Pengendalian Pencemaran Udara.Siddiqui, K. M., Sahay, K., & Giri, V. K. (2014). Health Monitoring and Fault Diagnosis in Induction Motor- A Review. International Journal of Advanced Research in Electrical, Electronics and Instrumentation Engineering, 3(1), 2320–3765.Squirrel, I. (n.d.). Lecture 1 Three-phase Induction Motor Construction and Principle of Operation 2 . Induction Motor Types : 1–9.Sri Kusumadewi, H. P. (2010). Fuzzy logic application for decision support. Graha Ilmu.Teknologi, I., & Seni, D. (2020). Analisa Thermal Overload Relay ( TOR ) Type Lrd08c Pada Sistem Proteksi Motor 3 Fasa Belt Conveyor. 1, 79–90.US Department of Energy. (2014). Determining Electric Motor Load Ranges. Motor Challenge, 1, 1. https://www.energy.gov/sites/prod/files/2014/04/f15/10097517.pdfWaide, P., & Brunner, C. U. (2011). Energy-Efficiency Policy Opportunities for Electric Motor-Driven Systems. Internationale Energy Agency, na(na), 132.